PENGARUH PERSEPSI SISWA ATAS PENGGUNAAN METODE PEMBELAJARAN TANYA JAWAB, DISKUSI, DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA SMA NEGERI DI KECAMATAN KEBAYORAN BARU JAKARTA SELATAN - Siti Askariyah; Edi Siregar (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
This study is aimed to determine the impact of students' perceptions on the use of learning methods of debriefing, discussion and motivation to excel on learning outcomes in mathematics. The sampling technique is proportionate stratified random sampling that by using Solvin formula provides 204 students from a population of 418 samples. Data collection technique of students’ perceptions, discussion, and motivation to excel has been done by using primary data by questionnaire. Mathematics learning result is obtained from secondary data by using multiple-choice question result in the final exam of the third semester. While the methods of analysis used in this study were multiple linear regression. The result of this study indicates that there is significant impact of studens’ perceptions on the use of debriefing as learning method on the result of mathematic learning outcomes, that there is significant impact of motivation to excel on the result of mathematic learning outcomes, that there is significant impact of students’ perception on the use of debriefing, discussion, and motivation to excel altogether on the result of mathematic learning outcomes. Nevertheless, there is no significant impact of students’ perception on the use of discussion as a learning method on the result of mathematic learning outcomes.